DOI: 10.21007/etd.cghs.2008.0041
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of African American Women's Perceived Health Status in the Context of Caring for a Relative With End Stage Renal Disease

Abstract: The purposes of this study of African American women who were family caregivers of persons with end stage renal disease (ESRD) were to: (1) identify their perceived health status and changes in perceived health status since assuming the caregiver role, (2) document the association between objective health status and caregiver age, (3) document the relationship between age and perceived health status, (4) identify demographic and subjective and objective health factors that predict perceived health status, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 98 publications
(164 reference statements)
0
8
0
2
Order By: Relevance
“…2006) and that the patients’ illness influences the next of kin’s own health and quality of life (Belasco & Sesso 2002, Acaray & Pinar 2005, Ziegert et al. 2006, Byers et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2006) and that the patients’ illness influences the next of kin’s own health and quality of life (Belasco & Sesso 2002, Acaray & Pinar 2005, Ziegert et al. 2006, Byers et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, caring for people undergoing HD can be a heavy burden (Belasco & Sesso 2002) and influences the carers own health (Ziegert et al. 2006, Byers et al. 2009) and quality of life (Belasco & Sesso 2002, Alvarez‐Ude et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, physically healthy individuals with high levels of emotional distress may view themselves as physically ill (Olfson, Gilbert, Weissman, Blacklow, & Broadhead, 1995); this perception has also been found to be associated with increased use of physician services (Miilunpalo et al, 1997). In addition, negative changes in self-reported health were found to be frequently associated with stress and tension in a sample of caregivers (Byers, Beard, & Wicks, 2009). Cognitive-perceptual factors (such as perceived health status and health self-efficacy) have been found to influence the maintenance of health-promoting behaviors, including seeking health care services when illness' symptoms are suspected (Jackson, Tucker, & Herman, 2007).…”
Section: Psychosocial Factors and Illness Behaviormentioning
confidence: 99%
“…12 Shouldering this burden could in turn influence the next of kin's own health. 13,14 Haemodialysis units have been described as having dehumanising effects on patients. Research has indicated that nurses working in haemodialysis units have a biomedical focus and that the complex needs of older patients undergoing haemodialysis are not often met.…”
Section: Introductionmentioning
confidence: 99%